Students of San Jose Secretarial School - Johnson, Charles Elllis (photographer):::Creator::::::::::::
Students of the San Jose Secretarial School came together for a group photograph in what appears to be the current Plaza de Cesar Chavez in downtown San Jose. The men in the photograph mostly fill the back row. City buildings line the background of the photograph, and the San Jose Post Office is most visible behind the large palm tree, near the center left of the photograph.